Pemanfaatan Teknologi Drone untuk Penataan Promosi Kawasan Wisata Desa Rindu Hati - Budi Harlianto; Arif Ismul Hadi; Suwarsono Suwarsono (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2022)
Based on the results of the Focus Group Discussion (FGD) between Rindu Hati Village and LPPM Unib, 16 problems were identified. Based on these problems, there are 2 problems (Structure of Tourism Villages and Blockages in Promotion). This service aims to create a map of the existing condition of the tourist area and a video profile of the tourist area of Rindu Hati Village that can be used for promotion via the internet or social media. Implementation methods include problem identification and literature review. Then the data collection process in the form of spatial and non-spatial data such as the coordinates of tourist sites is taken using GPS, videos, photos and other non-spatial data through interviews with POKDARWIS Rindu Hati Village. Data management is done by using mapping and video editing software. The location of the tourist attraction in Rindu Hati Village which is closest to the center of the village is Glamping (03o 42' 41.30” South Latitude and 102o 31' 37.92” East Longitude), Camping Ground (03o 42' 41.25” South Latitude and 102o 31' 39 ,06” East), Waterfall (03o 44' 18.03” South Latitude and 102o 33' 48.42” East Longitude), Batu Jung (03o 43' 38.49” South Latitude and 102o 32' 31.89” East), Lake Telaga Putri (03o 44' 29.83” South Latitude and 102o 33' 23.87” East Longitude). Videos uploaded to the youtube account "Pengabdian IPTEKS 2021" https://youtu.be/nZj9Mx6K4yU (video 1), https://youtu.be/bbwQNjcoxK0 (video 2), and https://youtu.be/qMPDaE4V2qM ( videos 3). Keywords: Spatial, Rindu Hati, Glamping, Promotion Bedasarkan hasil Focus Group Discussion (FGD) antara pihak Desa Rindu Hati dengan LPPM Unib 16 masalah teridentifikasi. Berdasarkan masalah-masalah tersebut ada 2 masalah (Penataan Desa Wisata dan Sumbatan Dalam Promosi). Pengabdian ini bertujuan untuk membuat peta kondisi eksisting kawasan wisata dan vedio profil kawasan wisata Desa Rindu Hati yang dapat digunakan untuk promosi melalui internet atau media sosial. Metode pelaksanaan meliputi identifikasi masalah dan kajian literatur. Kemudian dilakukan pengambilan data yang meliputi data spatial dan juga data non spasial seperti pengambilan titik kordinat lokasi wisata dengan menggunakan GPS, video dan foto menggunakan drone atau camera digital serta data-data non spatial lainya yang dilakukan dengan wawancara terhadap POKDARWIS Desa Rindu Hati. Pengelolaan data dilakukan menggunakan software pemetaan dan editing video. Lokasi objek wisata Desa Rindu Hati yang paling dekat dengan pusat desa adalah Glamping (03o 42’ 41,30” LS dan 102o 31’ 37,92” BT), Camping Ground (03o 42’ 41,25” LS dan 102o 31’ 39,06” BT), Air Terjun (03o 44’ 18,03” LS dan 102o 33’ 48,42” BT), Batu Jung (03o 43’ 38,49” LS dan 102o 32’ 31,89” BT), Danau Telaga Putri (03o 44’ 29,83” LS dan 102o 33’ 23,87” BT). Video yang diupload ke akun youtube “ Pengabdian IPTEKS 2021”  https://youtu.be/nZj9Mx6K4yU (video 1), https://youtu.be/bbwQNjcoxK0 (video 2), dan https://youtu.be/qMPDaE4V2qM (video 3).